Pendampingan Terhadap Dampak Bahaya Bullying di Dunia Pendidikan - Islahudin, Islahudin; Supriadi, Pemas; Tophani, Ira; Safitriani, Desi; Nurafriani, Nurafriani; Jariyah, Ainun (Abdimas Mandalika, 2025)
Abstract:  Bullying is an act that is deliberately carried out by the perpetrator to harm the victim, not a form of negligence but a truly deliberate act. This service activity has a partner, namely SMPN 4 Keruak. The objectives of this service are 1) to provide socialisation for SMPN 4 Keruak students about the impact of bullying; 2) to provide assistance for SMPN 4 Keruak students to avoid bullying activities. The method used consists of 4 steps, namely 1) Preparation stage, 2) Implementation stage, 3) Implementation stage, and 4) Monitoring and evaluation. Based on the results of the socialisation and implementation of community service, it can be concluded that 1) Participation in the socialisation was very high, with more than 80% of students and teachers at SMPN 4 Keruak attending the sessions; 2) After the mentoring activities, evaluation through questionnaires showed an increase to 85% of students and teachers who understood the risks of bullying, both in terms of victims and perpetrators so that bullying activities could be minimised optimally.Abstrak: Bullying adalah suatu tindakan yang sengaja dilakukan oleh pelaku untuk menyakiti korban, bukan suatu bentuk kelalaian namun tindakan yang betul-betul disengaja. Kegiatan pengabdian ini memiliki mitra yaitu SMPN 4 Keruak. Tujuan pengabdian ini yaitu 1) memberikan sosialisasi bagi siswa SMPN 4 Keruak tentang dampak bullying; 2) memberikan pendampingan bagi siswa SMPN 4 Keruak agar terhindar dari kegiatan bullying. Metode yang digunakan terdiri dari 4 langkah yaitu 1) Tahap persiapan, 2) Tahap pelaksanaan, 3) Tahap implementasi, dan 4) Monitoring dan evaluasi. Berdasarkan hasil sosialisasi dan implementasi pengabdian kepada masyarakat tersebut dapat disimpulkan yaitu 1) Partisipasi dalam sosialisasi sangat tinggi, dengan lebih dari 80% siswa dan guru di SMPN 4 Keruak hadir dalam sesi-sesi yang diselenggarakan; 2) Setelah kegiatan pendampingan, evaluasi melalui kuesioner menunjukkan peningkatan menjadi 85% siswa dan guru yang mengerti risiko bullying, baik dari sisi korban maupun pelaku sehingga kegiatan bullying dapat diminamilisir secara optimal.